Legal Methods: How to work with legal arguments - Möllers, Thomas M. J. (Verlag C.H.BECK Recht - Wirtschaft - Steuern, 2021)
Möllers Legal Methods Legal decisions are accepted if they are well reasoned. German law is exemplary for its technique of legal interpretation and legal construction. This landmark book provides lawyers with more than a hundred legal argumentation figures that are used by lawyers across Europe and the world to justify their legal decisions. It aims to put lawyers in a position to develop legal solutions step by step, and to increase the cogency of their argumentation. Using an interdisciplinary and legal-doctrinal context, it looks at legal sources, traditional and modern concepts of argumentation, the challenging substantiation and construction of law, the influence of the constitution and European law as a higher-ranking law, determination of the limits of permissible further development of the law and – very relevant for legal practice – the hermeneutics of facts.